2005
DOI: 10.1007/s00415-005-0748-5
|View full text |Cite
|
Sign up to set email alerts
|

Interferon beta in relapsing–remitting multiple sclerosis

Abstract: Interferon beta is safe and well tolerated. The various registered interferon beta drugs provide a comparable efficacy in a large non-selected cohort of RRMS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…These results are in line with other short- and long-term real-world postmarketing studies [11,12,13,14,15,16,17,18,19,20,21]. Nevertheless, 2 previous head-to-head trials, EVIDENCE [9] and INCOMIN [10], showed superior efficacy for SC IFNβ compared with IM IFNβ in terms of time to the first clinical MS relapse on study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These results are in line with other short- and long-term real-world postmarketing studies [11,12,13,14,15,16,17,18,19,20,21]. Nevertheless, 2 previous head-to-head trials, EVIDENCE [9] and INCOMIN [10], showed superior efficacy for SC IFNβ compared with IM IFNβ in terms of time to the first clinical MS relapse on study.…”
Section: Discussionsupporting
confidence: 73%
“…Several open-label, postmarketing, observational studies have reported similar efficacy for the three different IFNβ preparations [11,12,13,14,15,16,17,18,19], but only a few have compared these DMTs and GA [20,21]. There is only one report in the literature comparing the effects of all four different immunomodulatory therapies on MS disease progression in patients with relapsing-remitting MS (RRMS); however, the study groups were quite imbalanced, and the reported differences in hazard ratios between the DMTs were attributed to selection bias [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, and in accordance with previous long-term follow-up studies [26], [27], interferon beta-1b was associated with a favorable tolerability and safety profile and no unexpected or serious AEs were recorded.…”
Section: Discussionsupporting
confidence: 90%
“…Two large patient registries have also been established in Canada which have followed essentially all patients in a provincial catchment area over more than 15 years [4, 5]. Although specific prospective cohorts of patients starting interferon-β treatment for the first time have been established [6], we are not aware of any such prospective cohorts of patients starting GA.…”
Section: Introductionmentioning
confidence: 99%